Integrating Educational Foundations with Islamic Education: A Critical Analytical Study - Yovi, Febri Yonanda; Ilmi, Darul (El-Rusyd, 2025)
This article examines the integration of educational foundations with Islamic education principles to strengthen both theoretical understanding and contemporary educational practice. Educational foundations comprising philosophical, psychological, sociological, historical, juridical, curricular, cultural, technological, economic, and religious dimensions serve as the fundamental basis for determining the direction and objectives of education. From an Islamic perspective, education adopts a holistic orientation that emphasizes not only intellectual development but also moral, spiritual, and character formation. This study employs a qualitative descriptive approach using content analysis to explore the conceptual relationship between modern educational foundations and Islamic educational values. The findings indicate a strong integrative relationship, particularly in the development of human potential, character education, and holistic learning orientation. The discussion demonstrates that this integrative framework offers a relevant response to 21st-century educational challenges, including moral degradation, rapid technological advancement, and future-oriented learning demands. This article contributes conceptually by reinforcing the position of Islamic educational foundations within the contemporary global educational discourse.